Safety and efficacy of remimazolam in mechanical ventilation in the ICU: a protocol for systematic evaluation and meta-analysis - Li Liu; Xuelian Yang; Yulian Yang; Gelan Miao; Chaobing Yang; Xianying Lei (BMJ Open)
Introduction Remimazolam is a novel ultra-short-acting benzodiazepine that allosterically modulates γ-aminobutyric acid type A receptors to induce sedative effects. Remimazolam was approved by China for procedural sedation in 2020. Intensive care unit (ICU) patients frequently exhibit impaired liver and renal function as well as haemodynamic instability; thus, the pharmacokinetic properties of remimazolam may offer advantages for ICU sedation. A comprehensive evaluation of the relevant studies warrants further discussion. This systematic review aims to compare the efficacy and safety of the novel intravenous anaesthetic remimazolam with that of commonly used anaesthetics in the ICU.Methods and analysis The following databases will be searched: Embase, Cochrane Library, PubMed, MEDLINE, Web of Science, CNKI and WanFang to retrieve relevant randomised controlled trials (RCTs). This protocol was developed by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols 2020. RCTs about the use of remimazolam for sedation during ICU mechanical ventilation will be included. Two investigators will independently screen articles and extract data according to predefined inclusion and exclusion criteria. Following a qualitative evaluation of each study, data analysis will be conducted using Review Manager 5.4 software. The planned start and end dates for the study were placed on 1 June 2024 and 31 October 2024, respectively.Ethics and dissemination This protocol for the systematic evaluation and meta-analysis does not involve individual patient data; thus, ethical approval is not required. This will be the first meta-analysis to assess the sedative efficacy and safety of remimazolam in the ICU and to provide evidence to inform clinical decision-making. The findings will be disseminated through conference presentations and publications in peer-reviewed journals relevant to the field.PROSPERO registration number CRD42024554425